2013
DOI: 10.1016/j.bpj.2013.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Molecular Mechanisms for Cell-Fate Selection in Budding Yeast through Mathematical Modeling

Abstract: The specification and maintenance of cell fates is essential to the development of multicellular organisms. However, the precise molecular mechanisms in cell fate selection are, to our knowledge, poorly understood due to the complexity of multiple interconnected pathways. In this study, model-based quantitative analysis is used to explore how to maintain distinguished cell fates between cell-cycle commitment and mating arrest in budding yeast. We develop a full mathematical model of an interlinked regulatory n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 66 publications
(50 reference statements)
3
18
0
Order By: Relevance
“…As reported previously, the Start point is accurately predicted by the nuclear Whi5 concentration independent of cell size, type and G1 duration2. Our recent research has also confirmed that Start can be characterized by entropy4, as entropy defines the height in the landscape of cell fate decision-making.…”
supporting
confidence: 86%
“…As reported previously, the Start point is accurately predicted by the nuclear Whi5 concentration independent of cell size, type and G1 duration2. Our recent research has also confirmed that Start can be characterized by entropy4, as entropy defines the height in the landscape of cell fate decision-making.…”
supporting
confidence: 86%
“…It is known that the selection of cell fate in response to internal and external stimuli is essential to a cell's life (24). Since the occurrence of bistability defines the switch between two different cell fates (25), these rich dynamical behaviors contribute to the specification and maintenance of cell fate.…”
Section: Dynamical Analysis For the Degree Model Of The Mapk Cascade mentioning
confidence: 99%
“…Due to the lack of G1 cyclins, check point analysis in cell cycle is unable to be developed in this model. In [7], G1 cyclins are taken into account, and a new model for analyzing the cell fate decision mechanism at the Start transition point is constructed. This model explains how the crosstalk between cyclins and signal pathways determines the cell fate decision.…”
Section: © Higher Education Press and Springer-verlag Berlin Heidelbementioning
confidence: 99%
“…Motivated by some previous works [5][6][7]10], a full mathematical model is built by combining the schematic diagrams in Figure 1A and Figure 1B. Several assumptions, which are listed below, simplify the model.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation